THz switching generation using a PANDA ring resonator for high speed computer communication - Punthawanunt, Suphanchai; Soysouvanh, Saysamone; Luangxaysana, Khanthanou; Mitatha, Somsak; Yoshida, Masahiro; Komine, Noriyuki; Yupapin, Preecha (My University, 2012)
A novel design of Terahertz (THz) switching generation for high speed computer used is proposed. The dense wavelength division multiplexing (DWDM) can be obtained by using a Gaussian or Soliton pluses propagating within a modified add-drop filter know as a PANDA ring resonator. The THz devices can made contributions to promising applications in high-speed switching, demultiplexing, and wavelength conversion of optical signals. Effective THz control is also essential for the potential application to ultrahigh-speed wireless digital interconnects for computer chips of the ultrahigh clock rates (> 10 GHz). In principle, the high density frequency (wavelength) can be generated and used to form the radio frequency identification (RFID), Ad-Hoc network and ubiquitous applications, moreover, the tiny device system is the another advantage, which can be constructed incorporating the available currently used system. In this paper is organized as follow: introduction, theory and the use of such a system in all proposed applications.